New indolo[1, 2‐c]quinazolines for single‐crystal field‐effect transistor: A united experimental and theoretical studies. (27th August 2021) - Puli, Venkat Swamy; Kilaru, Suresh; Bhongiri, Yadagiri; Marri, Sreenath Reddy; Tripathi, Anuj; Chetti, Prabhakar; Chatterjee, Anindita; Vukoti, Kiran Kumar; Pola, Someshwar
Abstract: Here, we account the synthesis and characterization of a series of symmetrical fused heterocyclic aromatic hydrocarbons (HAHs) with an indolo[1, 2‐ c ]quinazoline (IQ) as the core moiety. All the new HAHs IQ series were systematically investigated by using various spectroscopic methods. Furthermore, their photo‐physical properties were supported by density functional theory (DFT) and time‐dependent density functional theory (TDDFT) studies to support the experimental findings. The tetramethyl‐substituted indolo[1, 2‐ c ]quinazoline (TMIQ) compound is shown to exhibit the shifted type of π – π stacking interactions, which render this series as a new semiconducting material. Single‐crystal‐based field‐effect transistor devices of TMIQ exhibited efficient charge transport behavior, giving a p‐channel field‐effect mobility of 0.25 cm 2 V −1 s −1 with an on/off ratio of 5 × 10 5 . Abstract : Synthesis of new fused heterocyclic aromatic hydrocarbon‐based IQ series and their single crystal field‐effect transistors have been shown.